Soil organic matter interactions along the elevation gradient of the James Ross Island (Antarctica) - V. Vlček; D. Juřička; M. Valtera; H. Dvořáčková; V. Štulc; M. Bednaříková; J. Šimečková; P. Váczi; M. Pohanka; P. Kapler; M. Barták; V. Enev (SOIL)
Around half of the Earth's soil organic carbon (SOC) is presently stored in the Northern Hemisphere permafrost region. In polar permafrost regions, low temperatures particularly inhibit both the production and biodegradation of organic matter. Under such conditions, abiotic factors such as mesoclimate, pedogenic substrate or altitude are thought to be more important for soil development than biological factors. In Antarctica, biological factors are generally underestimated in soil development due to the rare occurrence of higher plants and the short time since deglaciation. In this study, we aim to assess the relationship between SOC and other soil properties related to the pedogenic factors or properties. Nine plots were investigated along the altitudinal gradient from 10 to 320 m in the deglaciated area of James Ross Island (Ulu Peninsula) using a parallel tea-bag decomposition experiment. SOC contents showed a positive correlation with the content of easily extractable glomalin-related soil protein (EE-GRSP; Spearman r=0.733, P=0.031) and the soil buffering capacity (expressed as ΔpH; Spearman r=0.817, P=0.011). The soil-available P was negatively correlated with altitude (Spearman r=-0.711<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="7148a909bb34bdb2df1009de6e6c5689"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-10-813-2024-ie00001.svg" width="55pt" height="10pt" src="soil-10-813-2024-ie00001.png"/></svg:svg>, P=0.032), and the exchangeable Mg was negatively correlated with the rock fragment content (Spearman r=-0.683<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="367107d415f8d56a3622e3ec206d61c1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-10-813-2024-ie00002.svg" width="55pt" height="10pt" src="soil-10-813-2024-ie00002.png"/></svg:svg>, P=0.050). No correlation was found between the available mineral nutrients (P, K, Ca and Mg) and SOC or GRSP. This may be a consequence of the inhibition of biologically mediated nutrient cycling in the soil. Therefore, the main factor influencing nutrient availability in these soils does not seem to the biotic environment; rather, the main impact appears to stem from the abiotic environment influencing the mesoclimate (altitude) or the level of weathering (rock content). Incubation in tea bags for 45 d resulted in the consumption and translocation of more labile polyphenolic and water-extractable organic matter, along with changes in the C content (increase of up to +0.53 % or decrease of up to −1.31 % C) and a decrease in the C:N ratio (from 12.5 to 7.1–10.2), probably due to microbial respiration and an increase in the abundance of nitrogen-binding microorganisms. Our findings suggest that one of the main variables influencing the SOC/GRSP content is not the altitude or coarse-fraction content (for which a correlation with SOC/GRSP was not found); rather, we suspect effects from other factors that are difficult to quantify, such as the availability of liquid water.